Dimensions of the Suckling Pig - Smith, Benjamin C.; Ramirez, Brett C. (Frontiers in Animal Science, 2021)
The rising prewean mortality rates in swine production are a great economic and production burden to the swine industry. The thermal environment for a piglet is commonly adapted to the piglet's specific needs with a key factor of surface area impacting all modes of heat transfer. The current standard for pig dimensions was originally accepted in 1968 and has yet to be updated with clear data from piglets during lactation. The objective of this study was to collect and evaluate the dimensions of body weight, length, height and width of piglets during lactation. Eight litters from geriatric sows (commercial cross breds) were utilized in this study with data collected every day from birth to weaning (23 to 32 days of age). The evaluation of the dimensions with effects of litter size and sex showed that sex of the piglet does not have a significant impact on dimensions while litter size does. The piglets in this study were smaller than the standard at birth, likely attributed to changes in genetics and an increase in total born. The results of this study showed a slight difference in dimension at the heavier weights to a study with nursery pigs however there are differences in genetics. The data and equations presented in this study will be valuable for the design of creep areas and supplemental heat sources to accommodate the size of modern piglets during lactation.